Role of Entrepreneurial Marketing in increasing product innovation during a pandemic: A Case Study on MSMEs managed by students in Jakarta - Prihadini, Diana; Krishantoro, Krishantoro (Technium Social Sciences Journal, 2021)
The MSME business is one of the sectors most affected by the Corona Virus (Covid-19) outbreak. There are at least 949 reports from cooperatives and micro, small and medium enterprises in Indonesia (MSMEs) affected by the Corona virus (Covid-19) outbreak. However, this is different from MSME which is managed by students. Many of them are actually able to survive during the pandemic and even reap greater profits than before the pandemic. Therefore, this research is intended to answer the question of how MSME students apply entrepreneurial marketing in increasing their business and how MSME students can enrich their business with product innovations. This is a qualitative research using a case study approach. Data collection was obtained from the results of semi-structured interviews with 4 groups of students who manage MSMEs in the fields of culinary, shoes, clothing and English course services. The results of this study prove that MSME managed by students can run well during a pandemic and even become more successful after making changes based on foresight to observe existing opportunities, and the ability to generate new ideas. In addition, the courage to face risks is also very necessary. In addition, this study also proves that MSME in the culinary field and English course services have managed to survive during the pandemic by carrying out incremental innovation, meanwhile, MSME in the shoes and clothing sector has carried out radical innovation both in components (modular) and systems (architectural).